A near-uniform fluctuation of ocean bottom pressure and sea level across the deep ocean basins of the Arctic Ocean and the Nordic Seas. (May 2015) - Fukumori, Ichiro; Wang, Ou; Llovel, William; Fenty, Ian; Forget, Gael
Graphical abstract: Highlights: A near-uniform barotropic fluctuation is identified across the deep Arctic basins. Winds along the region's continental slopes are the primary forcing. Coastally trapped waves transport the anomalies underlying the variation. The basins' potential vorticity distribution controls the fluctuation's extent. Model adjoints provide an effective means to study causal mechanisms. Abstract: Across the Arctic Ocean and the Nordic Seas, a basin-wide mode of ocean bottom pressure and sea level fluctuation is identified using satellite and in situ observations in conjunction with a global ocean circulation model and its adjoint. The variation extends across the interconnected deep ocean basins of these semi-enclosed Arctic seas, collectively called the Arctic Mediterranean, with spatially near-uniform amplitude and phase. The basin-wide fluctuation is barotropic and dominates the region's large-scale variability from sub-monthly to interannual timescales. The fluctuation results from bifurcating coastally trapped waves generated by winds along the continental slopes of the Arctic Mediterranean and its neighboring seas, including the North Atlantic Ocean. The winds drive Ekman transport across the large bathymetric gradients, forcing mass divergence between the shallow coastal area and the deep ocean basins and creating ocean bottom pressure anomalies of opposite signs in the two regions. The anomalies rapidly propagate away as barotropic coastally trapped waves with the coast and continental slope as respective boundaries. The waves subsequently bifurcate at the shallow straits connecting the Arctic Mediterranean with the rest of the globe. The straits transmit the shallow anomalies but not the deep variations, thereby inhibiting the anomalies' mutual cancelation by geographically separating the two. Anomalies that enter the deep Arctic basins equilibrate uniformly across the domain characterized by a homogeneous depth-integrated planetary potential vorticity distribution. The potential vorticity's steep gradient that borders the basins shields the region from neighboring shallow variations, giving rise to the observed spatially confined fluctuation. Compensating anomalies outside the Arctic adjust similarly across the rest of the globe but are comparatively negligible in amplitude because of the global ocean's larger area relative to that of the deep Arctic Mediterranean. The study, from a technical perspective, illustrates the utility of a model's adjoint in identifying causal mechanisms underlying a complex system.